Two new species of Artocarpus (Moraceae) from Thailand and Vietnam - Gardner, Elliot M.; Chaveerach, Arunrat; Sudmoon, Runglawan; Zerega, Nyree J.c. (Phytotaxa, 2020)
Recent taxonomic work on Artoarpus has revealed two undescribed species from Thailand and Vietnam. Artocarpus rubrosoccatus, endemic to peninsular Thailand, resembles A. lacucha but is distinguished by its deep red clavate staminate inflorescences. Artocarpus montanus is found in the montane regions of southern and central Vietnam, and perhaps also in Thailand. This species resembles the vegetative parts of A. lowii and A. excelsus, but A. montanus differs in its longer syncarp processes and its geographic distribution. The vast majority of Artocarpus species are found in tropical lowlands, and A. montanus, along with A. excelsus, represent the only known members of the genus that are restricted to montane habitats. The provisional conservation assessment of both new species is Near Threatened, because although their known areas of occupancy are restricted, both occur in protected areas.